David Michael Smith, William G. Cavanagh and Angelos Papadopoulos, The Wider Island of Pelops. Studies in Prehistoric Aegean Pottery in Honour of Professor Christopher Mee. - Dickinson , Oliver (Journal of Greek Archaeology, 2024)
The core of this collection of 17 contributions is made up of papers presented at a conference organised by two of Chris Mee‘s former students and held at the British School at Athens in 2017 to honour his memory; other papers were offered by friends and colleagues who had worked with him. The result may be a bit more wide-ranging than the original conference was, but this is a positive outcome, for despite the impression that might be given by the secondary title of the book, the majority of them are concerned with much more than just pottery, often presenting essentially new material of considerable interest. A useful preface by the editors summarises their topics and where they fit into the Neolithic-Bronze Age sequence of the Aegean.